HUBUNGAN KEKUATAN OTOT TUNGKAI DAN KECEPATAN LARI 60 METER DENGAN HASIL LOMPAT JANGKIT PADA SISWA PUTRA KELAS XI IS SMA PGRI PEKANBARU - Muhammad Hendri Hendri; Ramadi '; Kristi Agust Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problem in this research was found when the writer does an observation in the field. The writer found several weaknesses in jumping ,those are less of leg muscle strength and running speed at time of triple jump, which make the result was less than maximum, the purpose of this study was to determine the relationship leg muscle strength and running speed of 60 meters with a triple jump results in grade two social sciences sma pgri pekanbaru. The sample in this study was random, researchers took a sampling technique focuses on technique random sampling. To obtain research data used leg dynamometer tests for leg muscle strength, speed test run 60 meters for speed, and the triple jump results for triple jump. The data obtained was analyzed by using a sample moment product correlation. Based on the data analysis, correlation 12X1